BIOTEKNOLOGI, SEBUAH ILMU MASA DEPAN YANG MENJANJIKAN - Wahyono, Poncojari (Jurnal Bestari, 2001)
Biotechnology is to apply science concerning the animate creature and technology involve the biological processed application of animate creature (its biological cell process) to create industrial product and environmental processing. It uses a cheap labor service. Because the labor includes bacteria, fungi, plant cells, and animal cells are the main component of industrial process. Nowadays in Indonesia, biotechnology willy nilly must encourage an industrial improvement. As matter of fact, a nation that acquires technology should take in hand the world as it occurs in this biotechnology. We will have nothing and get behind, when we do not work hard to enrich it.